Analysis of Factors Influencing the Success of Forward and Backward Rolls in Elementary School Students in Kayong Utara Regency - Dody Arifahmi H.; Zusyah Porja Daryanto; Suriani Sari (CV. INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: Floor gymnastics, particularly forward and backward rolls, is a fundamental component of elementary school physical education. However, many students experience difficulty performing these movements successfully due to various contributing factors. This study aims to identify and analyze the dominant internal and external factors influencing the success of forward and backward rolls among elementary school students in Kayong Utara Regency. Materials and methods: This research employed a survey method with a descriptive qualitative approach. A questionnaire consisting of 30 items covering five indicators—balance, self-confidence, repulsion, flexibility, and the use of inclined mats—was distributed to 21 PJOK teachers from Teluk Batang and Sukadana sub-districts. The collected data were analyzed using percentage classification to determine factor dominance. Results: Findings showed that balance was the most influential internal difficulty factor (42.86%), followed by self-confidence (28.57%), repulsion (23.81%), and flexibility (19.05%). Additionally, an external factor—the use of modified inclined mats—demonstrated an equally high influence (42.86%), supporting students' learning success in rolling movements. Conclusions: Students’ success in performing forward and backward rolls is significantly influenced by internal factors such as balance, confidence, strength, and flexibility, as well as external support in the form of appropriate learning media. Strengthening balance training, motivational support, proper technique instruction, flexibility exercises, and the strategic use of inclined mats are recommended to enhance learning outcomes in floor gymnastics.